THE IMPORTANCE OF DEPOSITS IN STRENGTHENING THE RESOURCE BASE OF COMMERCIAL BANKS - Isroilova Sitorabonu Qodirjon qizi (Modern American Journals, 2025)
The article describes the importance of deposits in the resources of commercial banks. The deposit policy is one of the main parts of the general banking policy, and the internal and external factors affecting it are highlighted. Statistical and econometric analysis of deposit performance indicators of commercial banks has been carried out, and scientific proposals and practical recommendations have been formulated related to the implementation and strengthening of the effective deposit policy of commercial banks.
Keywords: Deposit, deposit types, deposit policy, deposit operations, term deposits, liquidity.